Nano-adjuvanted dry powder vaccine for the mucosal immunization against airways pathogens - Canelli, Elena; Ferrari, Luca; Borghetti, Paolo; Candela, Francesco; Abiakam, Nkemjika Sopuru; Bianchera, Annalisa; Buttini, Francesca; Magi, Gian Enrico; Sonvico, Fabio; Martelli, Paolo; Bettini, Ruggero (Frontiers in Veterinary Science, 2023)
Nasal vaccination has been shown to provide optimal protection against respiratory pathogens. However, mucosal vaccination requires the implementation of specific immunization strategies to improve its effectiveness. Nanotechnology appears a key approach to improve the effectiveness of mucosal vaccines, since several nanomaterials provide mucoadhesion, enhance mucosal permeability, control of the antigen release and adjuvant effects. Mycoplasma hyopneumoniae is the main causative agent of enzootic pneumonia in pigs, a respiratory disease responsible for considerable economic losses in the pig farming worldwide. The present work developed, characterized, and tested in vivo an innovative dry powder nasal vaccine, obtained from the deposition on a solid carrier of an inactivated antigen and a chitosan-coated nanoemulsion, as an adjuvant. The nanoemulsion was obtained through a low-energy emulsification technique, a method which allowed to achieve nano droplets in the order of 200 nm. The oil phase selected was alpha-tocopherol, sunflower oil, and poly(ethylene glycol) hydroxystearate used as non-ionic tensioactive. The aqueous phase contained chitosan, which provides a positive charge to the emulsion, conferring mucoadhesive properties and favouring interactions with inactivated M.hyopneumoniae. Finally, the nanoemulsion was layered with a mild and scalable process onto a suitable solid carrier (i.e. lactose, mannitol, or calcium carbonate), to be transformed in a solid dosage form for administration as dry powder. In the experimental study, the nasal vaccine formulation with calcium carbonate was administered to piglets and compared to intramuscular administration of a commercial vaccine and of the dry powder without antigen, aimed at evaluating the ability of IN vaccination to elicit an in vivo local immune response and a systemic immune response. Intranasal vaccination was characterized by an early and intense immune response in the nasal mucosa at 2 and 7 days post-vaccination, elicited comparable levels of Mycoplasma-specific IFN-γ secreting cells and comparable, if not higher, responsiveness of B cells expressing IgA and IgG in peripheral blood mononuclear cells, with those detected upon a conventional intramuscular immunization. In conclusion, this study illustrates a simple and effective strategy for the development of a dry powder vaccine formulation for nasal administration which could be used as alternative to current parenteral commercial vaccines.